How Economic Rights for SMEs Protected? Analysis of National and International Property Rights Law - Waspiah, Waspiah; Rodiyah, Rodiyah; Latifiani, Dian; Arifin, Ridwan (Faculty of Law, Universitas Negeri Semarang, 2020)
Small and Medium Enterprises (SMEs) in Indonesia are growing rapidly and continuing to grow. These developments had a significant impact on economic growth for various sectors in Indonesia. However, the dynamics of the development of SMEs are still overshadowed by the unclear protection of rights relating to intellectual property, including economic rights for SMEs. In fact, this right becomes an important part that is regulated both in national and international legal rules. The purpose of this study is to determine and compare the implementation of the protection of economic rights for SMEs in Central Java Province, Indonesia. This research method uses interview techniques and direct observation in several SMEs in Central Java. This study found that the protection of economic rights for SMEs had not been maximally carried out, even the number of SMEs did not yet obtain guaranteed recognition of the brand rights and copyrights of their products. This study concludes that in applying protection to economic rights for SMEs, collaboration between sectors and ministries is needed, not only the Ministry of Law and Human Rights, but also Industry, Trade and Economy.